APOPTOSIS INDUCTION OF EPIFRIEDELINOL ON HUMAN CERVICAL CANCER CELL LINE - Yang, Jie; Fa, Jing; Li, Bingxing (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Present investigation evaluates the antitumor activity of epifriedelinol for the management of cervical cancer by inducing process of apoptosis. Methods: Human Cervical Cancer Cell Line, C33A and HeLa were selected for study and treated with epifriedelinol at a concentration of (50-1000 μg/ml). Cytotoxicity of epifriedelinol was estimated by MTT assay and induction of apoptosis was assessed by estimating the activity of caspase 3, 8 and 9 enzyme, apoptosis assay and translocation of cytochrome c. Moreover an expression of several proteins that plays role in the apoptosis process was estimated by western blot method. Results: Result of the study suggested that treatment with epifriedelinol significantly decrease the viability count of cancerous cell in a dose perndent manner and also enhances the formation of oligonucleosome in both the cell lines. However activity of caspase enzymes and translocation of cytochrome c were enhanced after treatment with epifriedelinol. It was also observed that epifriedelinol treatment alters the ratio of pro-apoptotic to anti-apoptotic proteins and enhances the expressions of inhibitor of apoptosis proteins (IAP). Conclusion: Result of our study proves the anticancer activity of epifriedelinol in cervical cancer by inducing apoptosis as treatment with it enhances the production of oligonucleosomes, translocation of cytochrome c and activity caspase enzymes.